A Serial Mediation Approach to Goal Orientations, Learning Strategies and Achievement Outcomes on a Computer-Mediated English Program. (December 2021) - Rivers, Damian J.
Computer-mediated learning initiatives have recently increased due to the novel coronavirus pandemic. Implications are thus created for self-regulation, learning and achievement as computer-mediated learners face unique motivational and metacognitive demands. The current research uses a serial mediation approach to test the effect of goal orientations and the mediatory role of learning strategies on achievement among 195 Japanese university students on a 24-month computer-mediated English program. The tested model shows a good fit to the data and accounts for 28.5% of the achievement variance. Direct effects are observed between a performance-approach orientation and achievement. Mediation effects are also observed between a performance-approach orientation and achievement via a strategic approach to learning. In contrast, the effect of a mastery orientation on achievement is mediated via a strategic approach to learning. A mediated serial effect is also observed between a mastery orientation and achievement via a deep and strategic approach to learning. The challenges facing teachers and students of computer-mediated learning solutions in English as a foreign language (EFL) education and the importance of providing an informed experience that facilitates, supports and rewards adaptive motivations and approaches to learning are discussed.